Pelatihan Penulisan, Publikasi Artikel Ilmiah Penelitian pada Guru Madrasyah Tsanawiyah & Madrasyah Aliyah Swasta Al-Hakimiyah Paringgonan - Huda, Rahmat; Parapat, Lili Herawati; Khairul Amri; Lubis, Khatib (PAKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
This training aims to improve the writing and publication of scientific articles originating from research and community service efforts carried out by educators at Madrasah Tsanawiyah and Madrasah Aliyah Aliyah Paringgonan in May 2025. This training involved 20 educators from both levels of education with the aim of increasing teacher competence in the formulation and dissemination of research-oriented scientific works based on classroom actions and community service initiatives. Instructional content includes methodologies for the composition of scientific articles, criteria for selecting appropriate journals, and strategies for publication on national and international platforms. Using instructional methods that include lectures, discussions, and practical exercises, participants gain valuable experience in compiling articles that are considered suitable for submission to scientific journals. The results of this training show a significant increase in participants' understanding of the structural components of scientific writing, in addition to the development of several article drafts as initial outputs. This training is anticipated to be a basic step in fostering a culture of academic writing and publication in the madrasah environment.